The Wordsworth Dictionary Of Film Quotations - Ed. Crawley, Tony; Film & Video; History & Criticism; Performing Arts; Reference; Reference (Wordsworth Editions Ltd, 1994)
This essential guide for film fans contains over 2000 sparkling quotations and anecdotes encapsulating the wisecracks and sideswipes of the world.
Keywords: Film & Video; Film & Video; General; Performing Arts; Motion Pictures; Performing Arts